An emerging concern of medical waste management in Rohingya refugee camps at Cox’s Bazar, Bangladesh: existing practice and alternatives - Haque, Md. Rashedul; Chowdhury, Farah Noshin; Hossain, Abir; Akter, Rubaiya; Rahman, Md. Mostafizur (Frontiers in Environmental Science, 2023)
The plight of humanity in refugee camps is an age-old issue, as is the ever-increasing issue of waste management, especially medical waste. Though situations have improved in recent times for refugee camps, the same cannot be concurred about medical waste management, as it increases in amount every day. This is the first study on the refugee camp, which was conducted to assess the status of medical waste management and to quantify and characterize medical wastes disposed of in the Rohingya refugee Camp at Cox’s Bazar, Bangladesh. A cross-sectional, qualitative, and quantitative study was done. A total of 499 households were surveyed by KoBo Toolbox, along with 30 solid waste collectors were interviewed, and 21 solid waste management (SWM) plant workers were also surveyed. Monthly medical waste collection data from February to June 2022 was also collected. Data collection, processing, and statistical analysis were done using Origin Pro and SPSS software. It was found that the camps did not follow any specific guidelines for medical waste management except for a few segregations in health care facilities (HCF). Though 88% of the respondents were aware of the hazardous nature of medical waste, most of them disposed of these wastes in open places (49%), drains (44%), and 70% did not segregate it from regular waste at the household level. 73% of solid waste management workers find medical waste daily in communal bins. The HCF did not keep any records on the production of medical waste. Different types of medical waste were found in communal bins; glass bottles containing medicines were common among them. Data from the material recovery facility (MRF) of this camp showed that the highest amount of medical waste found in the communal bins was in April (65kg) during the seasonal change from spring to summer and the lowest in February (12.7kg). Moreover, HCF's existing medical waste management practices were analyzed with SWOT and DPSIR framework. Based on all the findings, a comprehensive on-site and off-site management plan for medical waste is also proposed here. That will help the concerned prepare a camp medical waste management guideline.